Health Sciences 2021
DOI: 10.35988/sm-hs.2021.195
|View full text |Cite
|
Sign up to set email alerts
|

Universiteto Studentų Gyvensenos Ypatumai Pandemijos Metu: Darbo Kompiuteriu Aplinka Ir Fizinis Aktyvumas

Abstract: COVID-19 pandemijos metu perėjimas prie nuotolinio mokymo(si) pakeitė universiteto studentų studijų aplinką ir veiklos pobūdį, pailgėjo darbo kompiuteriu laikas. Tuo laikotarpiu didėjo jaunų žmonių fizinis pasyvumas ir sė­dimos veiklos trukmė. Darbo tikslas − tirti universiteto studentų gyvenseną, darbo kompiuteriu aplinką ir fizinio aktyvumo ypatumus pandemijos metu. Tyrimas atliktas 2020 m., Lietuvos aukštosiose universitetinėse mokyklose, po pirmosios pandemijos bangos. Apklausoje dalyvavo 201 studentas: 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The subjects indicated that they had no experience with distance learning before the start of the coronavirus. Strukčinskaitė et al (2021) study revealed that during the pandemic, only a minority of students took regular breaks after spending many hours at the computer. The subjects mentioned inadequate work equipment and working environment, and most of them felt pain in various parts of the body.…”
Section: National Contextmentioning
confidence: 99%
“…The subjects indicated that they had no experience with distance learning before the start of the coronavirus. Strukčinskaitė et al (2021) study revealed that during the pandemic, only a minority of students took regular breaks after spending many hours at the computer. The subjects mentioned inadequate work equipment and working environment, and most of them felt pain in various parts of the body.…”
Section: National Contextmentioning
confidence: 99%
“…On the other hand, during the COVID-19 pandemic, the transition to distance education changed the study environment and the nature of activities of university students, the time spent working on a computer increased, and certain health problems became apparent. The study revealed (Strukčinskaitė et al, 2021) that during the pandemic, most students spent many hours a day at the computer, and only a minority took regular breaks. Finally, the COVID-19 pandemic exacerbated and accelerated the process of depersonalisation of academic life (Dagys, 2020), highlighted many challenges, related to the organisation and execution of the study process (Lamanauskas et al, 2022), for example, it is not known what the student actually does, and how his identification with the studies or the university in general takes place, the student's perception of the quality of the lectures, the student's opinion about the teaching content and forms.…”
Section: National Contextmentioning
confidence: 99%